A one-year unisexual Schistosoma mansoni infection causes pathologic organ alterations and persistent non-polarized T cell-mediated inflammation in mice - Sombetzki, Martina; Reinholdt, Cindy; Winkelmann, Franziska; Rabes, Anne; Koslowski, Nicole; Reisinger, Emil C. (Frontiers in Immunology, 2022)
In exhibiting gonochorism and phenotypic sexual dimorphism, Schistosoma spp. are unique among trematodes. Only females mating with male schistosomes can produce the highly immunogenic parasite eggs which determine the clinical picture of the disease schistosomiasis. The strong immune-modulatory effect of the eggs masks the influence of the adult worms. To shed light on the complexity of the immune response triggered by adult worms of Schistosoma mansoni, we performed a long-term unisexual infection experiment in mice. We were able to demonstrate that both male and female schistosomes can survive unpaired for one year in the murine host. Furthermore, unisexual S. mansoni infection leads to pronounced inflammation of the liver characterized by a non-polarized Th1/Th2 immune response, regardless of worm sex.